GENDER DAN FEMINISME DALAM ISLAM - Heri Junaidi; Abdul Hadi (Muwazah, 2010)
Feminism and gender is basically a simple concept where women just want to get justice in all matters, especially education, not to exceed man and nature. Because it gives the concept of gender-feminist groups depart from the differences of men and women that is due to be formed by the social differences are not judged by the natural aspect. The term feminism and gender with various forms of the concept and its implementation in conducting a lawsuit over the values subbordinasi women did not exist in Islam, because Islam itself does not distinguish the position of a person based on gender and gender bias does not exist in Islam. Islam put men and women in the same position and the same glory.